Central bank independence and sovereign debt crisis. Any link? - Kari Heimonen; Aleksandra Maslowska-Jokinen (Aboa Centre for Economics (ACE), 2014)
In this paper we ask if central bank independence could lead to a bad fiscal position of some countries. Introducing autonomous central bank without changing other policy habits could expose the country to greater temptation to borrow money. We think that introducing high degree of CBI creates illusion that these countries are of similar credibility as a borrower. It opens new possibilities to borrow money and to increase consumption, thus leading to greater indebtedness. We analyse if the size of improvement in CBI was connected with country's increase in debt. We hypothesise that some countries could misuse the benefits coming from CBI, would not introduce discipline in other parts of economic policy and not only continue spending but also increase their volumes thanks to wider options for borrowing. Panel data estimations results using EMU-14 confirm our hypotheses. Greater increase in CBI was related to greater increase in debt, both public and private. These results are confirmed with alternative models and varying definitions of central bank independence.
Keywords: C33; E02; E58; E61; 330; central bank independence; sovereign debt; private debt; sound money; panel data